An Exploratory Study of Preferred Learning Styles of Visually Impaired Children - Sumaira Chaudhary; Shaista Majid (JIE, 2023)
The research was designed to explore the learning styles preferred by the children with visual impairment. A survey was conducted to collect information from 50 males and 50 female students with visual impairment studying in grade six to ten at government special education schools for visually impaired in Rawalpindi and Islamabad, selected through simple random technique. The younger version of Visual, Aural, Read/write, and Kinesthetic (VARK) questionnaire containing four sub scales for each sensory modality was used as a research tool. The tool was administered after pilot testing. Results of this study showed that the reading/writing style of learning was the most preferred learning style by students with visual impairment. Gender differences were not found significant on visual and oral sub scales, whereas boys and girls were found significantly different on two learning styles; i) read/write, and ii) kinesthetic. The study concludes that reading/writing style of learning is the most preferred style by the visually impaired students and the visually impaired boys also take interest in kinesthetic style of learning. The study recommends the teachers of visually impaired students, to opt the teaching strategies as per their preferred style of learning; i.e. reading/writing style of learning.